Generalized Elastic Line Deformed on a Nonnull Surface by an External Field in the 3-Dimensional Semi-Euclidean Space E_1^3 - Gorgula, V. I.; Gürbüz, N. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We deduce intrinsic equations for a generalized elastic line deformed on the nonnull surface by an external field in the semi-Euclidean space E_1^3 and give some applications.